Efficient solutions of time versus cost transportation problems. Issue 3 (15th November 2022) - Muralidaran, C.; Venkateswarlu, B.
In time versus cost transportation problem, the time duration for shipping units and the unit cost for transporting are considered and is known as the classical transportation problem. In such situations, the main objective is to find effective solutions instead of just trying to minimise the total transportation cost. The balancing solution to this problem may be found by reaching a compromising solution in terms of both the criteria of cost and time. A new method is proposed to solve this problem named as root searching. It is an effort to discover a set of efficient solutions and the most efficient solution of the time versus cost transportation problems. Efficiency may be moderating the solutions devoid of extreme measures. One solution is to minimised total transportation time, and the other is to minimised total transportation cost. It shall certainly provide great benefit and support to decision-makers.